Impact of COVID-19 lockdown on endurance capacity of elite handball players - Fikenzer, S.; Fikenzer, K.; Laufs, U.; Falz, R.; Pietrek, H.; Hepp, P. (The Journal of Physical Fitness and Sports Medicine, 2020)
Background: The lockdown due to the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 has far-reaching consequences for professional sports in Germany. The aim of the present study was to investigate the impact of the 8-week lockdown on endurance capacity of elite male handball players.